Glis1 and oxaloacetate in nucleus pulposus stromal cell somatic reprogramming and survival - Lufkin, Leon; Samanta, Ankita; Baker, DeVaun; Lufkin, Sina; Schulze, JesslynHope; Ellis, Benjamin; Rose, Jillian; Lufkin, Thomas; Kraus, Petra (Frontiers in Molecular Biosciences, 2022)
Regenerative medicine aims to repair degenerate tissue through cell refurbishment with minimally invasive procedures. Adipose tissue (FAT)-derived stem or stromal cells are a convenient autologous choice for many regenerative cell therapy approaches. The intervertebral disc (IVD) is a suitable target. Comprised of an inner nucleus pulposus (NP) and an outer annulus fibrosus (AF), the degeneration of the IVD through trauma or aging presents a substantial socio-economic burden worldwide. The avascular nature of the mature NP forces cells to reside in a unique environment with increased lactate levels, conditions that pose a challenge to cell-based therapies. We assessed adipose and IVD tissue-derived stromal cells through in vitro transcriptome analysis in 2D and 3D culture and suggested that the transcription factor Glis1 and metabolite oxaloacetic acid (OAA) could provide NP cells with survival tools for the harsh niche conditions in the IVD.